2000
DOI: 10.1159/000028898
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bipedicular Advancement Flaps for Intrauterine Closure of Myeloschisis

Abstract: Several groups have begun to explore the feasibility and utility of intrauterine closure of myelomeningocele. A subset of these fetuses have defects which fall into the category of myeloschisis, and therefore have inadequate skin to enable primary closure. After considerable discussion, it was decided to utilize bipedicular flaps to close these lesions. The procedure is described, and representative examples are shown. To date, 13 of 56 fetuses have required this approach for closure in utero. While this techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 10 publications
1
33
0
2
Order By: Relevance
“…The average complication rates have been reported between 7.7% and 33%. 10,14,15,20 Our overall complication rate was only 8%. Compared with the literature, this is very low; these results verified the reliability of our guide.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The average complication rates have been reported between 7.7% and 33%. 10,14,15,20 Our overall complication rate was only 8%. Compared with the literature, this is very low; these results verified the reliability of our guide.…”
Section: Discussionmentioning
confidence: 60%
“…3,12 There is experimental and clinical evidence that in utero repair of MMCs may preserve neurological function. 15 However, this option is available in only a few centers; closure of an MMC defect is usually performed during the first hours after birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The entire maneuver takes about 5 min. Straightforward suturing as well as alternative ways to close the central skin defect, including lateral skin incisions [1,7,8] or implantation of skin substitutes (e.g., Alloderm TM [1,9], Epiflex ® (German Institute for Cell and Tissue Replacement GmbH, Berlin, Germany) (we used it twice, not published), or Integra Artificial Skin TM [10]), require similar amounts of time.…”
Section: Color Version Available Onlinementioning
confidence: 99%
“…In the literature, there is only one article [8] dealing with the problem of in utero skin reconstruction, although it is a frequent and clinically relevant topic. The authors reported using bipedicular bilateral advancement flaps for MS repair.…”
Section: Color Version Available Onlinementioning
confidence: 99%